2022
DOI: 10.1002/aelm.202200800
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Al2O3–TiO2 Conductive Oxide Interfaces as Defect Reservoirs for Resistive Switching Devices

Abstract: Resistive switching devices herald a transformative technology for memory and computation, offering considerable advantages in performance and energy efficiency. Here, a simple and scalable material system of conductive oxide interfaces is employed, and their unique properties are leveraged for a new type of resistive switching device. An Al2O3–TiO2‐based valence‐change resistive switching device, where the conductive oxide interface serves both as the bottom electrode and as a reservoir of defects for switchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Seok et al reported that trimethylaluminum (TMA), an Al precursor, creates V o and electrons by reducing the TiO 2 layer, resulting in the formation of 2DEG . This laterally conducting layer formed at the Al 2 O 3 /TiO 2 interface can be interpreted as an n-type semiconductor, where V o serves as a donor, and several researchers have proposed methods to harness this 2DEG as a V o reservoir for RRAM. Thus, a more compact, scaled S-RRAM can be constructed by establishing a vertical 2DEG and employing it as an electrode and controlling the V o concentration within the RRAM layer via thermal migration from the 2DEG through a minimized active switching region.…”
Section: Introductionmentioning
confidence: 99%
“…Seok et al reported that trimethylaluminum (TMA), an Al precursor, creates V o and electrons by reducing the TiO 2 layer, resulting in the formation of 2DEG . This laterally conducting layer formed at the Al 2 O 3 /TiO 2 interface can be interpreted as an n-type semiconductor, where V o serves as a donor, and several researchers have proposed methods to harness this 2DEG as a V o reservoir for RRAM. Thus, a more compact, scaled S-RRAM can be constructed by establishing a vertical 2DEG and employing it as an electrode and controlling the V o concentration within the RRAM layer via thermal migration from the 2DEG through a minimized active switching region.…”
Section: Introductionmentioning
confidence: 99%
“…A memristor is a resistance-switchable non-volatile device that was first defined by Chua in the last century as the fourth basic electronic component. 1 It has the advantages of energy-efficiency, 2 high speed, 3 simple structures, 4 easy integration, 5 and compatibility with traditional semiconductor manufacturing processes. 6 At the moment when Moore's Law is becoming increasingly shackled, memristors are considered to be the most potential candidates for next-generation non-volatile memory devices.…”
Section: Introductionmentioning
confidence: 99%
“…Several applications for this unique conducting layer have been published, for example, as a channel layer in a fieldeffect transistor or the bottom electrode of a conductive bridge random access memory device to enhance uniformity [1,2]. However, among the reported applications, the utilization of the 2DEG as an electrode of oxide-based resistive random access memory (OxRAM) is of particular interest [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, while the oxide electrolyte is stoichiometric, the leakage current decreases but the voltage required to form V o filaments increases. Because the 2DEG formed via the ALD process can be considered as an n-type semiconductor, where V o serves as a donor, this trade-off can be addressed by applying the 2DEG as an electrode of RRAM, where it plays the role of an oxygenscavenging layer for the oxide [4,7,12]. The resulting RRAM with the 2DEG has a low leakage current on account of the stoichiometric oxide electrolyte, and requires only a low voltage to form V o filaments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation